A Quasi-experimental Study to Assess Effectiveness of Information Booklet on Prevention of Respiratory Problems among Traffic Police in Metropolitan City - S. Rajput, Shivani; Sawant, Suchita; Gholap, Gayatri (International Journal of Nursing Research, 2023)
Introduction: Humans will never fit this environment; hence, perfect health is impossible. Health is the ability to adjust to changing life conditions. Air-filled and spongy lungs are on either side of the chest. The heart and mediastinum divide the thoracic cavity into two chambers. Pulmonary ventilation exchanges air with the lungs’ alveoli. Aim: The aim of the study was to study a Quasi-experimental Study to Assess Effectiveness of Information Booklet on Prevention of Respiratory Problems Among Traffic Police in Metropolitan City. Materials and Methods: The study employed a quantitative descriptive evaluative research design with one group pre-test and post-test research design. The sample included 60 traffic cops who met the inclusion criteria for the sample selection. The approach of non-probability convenient sampling was used. The Paired t-test was used to analyses the influence of an education booklet on traffic officers’ knowledge and behaviors regarding selected components of respiratory issue prevention. Results: The pre-test mean of traffic cop knowledge was 6.03, while the post-test mean was 19.85. The estimated t value 35 is more than the tabulated value 2.0 at the 5% level of significance. The mean of the traffic police procedures collected before the test was 1.68 and it jumped to 3.90 after the test. The estimated t value 14 is bigger than the tabulated value 2.0 at the 5% level of significance. Conclusion: Knowledge and practices in relation to selected aspects of prevention of respiratory problems among traffic police. The information booklet helped to increase the knowledge and practice of traffic police.